SFU’s Earthgazing VR Experience Can Help Astronauts Deal with Isolation (AR VR News, 2021)
Researchers at Simon Fraser University’s iSpace Lab have designed a virtual reality experience called ‘Earthgazing’ to help astronauts deal with isolation and confinement.
Keywords: mediaCoverage; proj--SIRIUS-earthgazing-newscoverage